University an inclusive education for persons of a condition intellectual disability and the social vision of neurosciences (Information Theory) - Vásquez Espinoza, Paola (2019)
This paper explains how a university is utilizing an inclusive education approach to help a student who has a condition of intellectual disability. We propose that neocortical development is different for every individual, which means that internal processes are being conditioned by external influences. By the same token, we have analyzed the current local regulations and norms regarding the concept of disability; in particular in reference to inclusion for students with special needs at the university level. Consequently, a research has been carried out to figure out the regulations that would help us interpret these aspects of especial education in Peru, as well as in Spain and Chile. Likewise, we propose that a closer look at the social aspects of the neurosciences would help create the appropriate space for educational inclusion in Peru.